Complexity in simulation-based education: exploring the role of hindsight bias. Issue 1 (January 2016) - Motavalli, Al; Nestel, Debra
Abstract Simulation-based education (SBE) has the potential to misrepresent clinical practice as relatively simplistic, and as being made safer through simplistic behavioural explanations. This review provides an overview of a well-documented and robust psychological construct -hindsight bias in the context of learning in healthcare simulations. Motivating this review are our observations that post-simulation debriefings may be oversimplified andbiased by knowledge of scenario outcomes. Sometimes only limited consideration is given to issues that might be relevant to management in the complexity and uncertainty of real clinical practice. We use literature onhindsight bias to define the concept, inputs and implications. We offer examples from SBE where hindsight bias may occur and propose suggestions for mitigation. Influences of hindsight biases on SBE should be addressed by future studies.